PHYTOSYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL ACTIVITY OF SILVER NANOPARTICLES USING Solanum seaforthianum Andrews - BASAVARAJESHWARI HEDAGINAL,; T. C. TARANATH, (International Journal of Pharma and Bio Sciences, 2016)
Phytosynthesis of nanoparticles using higher plants is cost effective, ecofriendly with large scale production potential. The present investigation reports a simple biological method for synthesis of biogenic silver nanoparticles using leaf extract of Solanum seaforthianum Andrews which served as a source of reducing and capping agents. The formation of silver nanoparticles was evident by change in colour of reaction mixture to dark brown due to surface Plasmon resonance. The characterization of biogenic silver nanoparticles was done with the help of UV-VIS spectrophotometer, Fourier Transform Infrared (FTIR) Spectroscopy, Atomic Force Microscope (AFM), High Resolution Transmission Electron Microscope (HR-TEM), X–Ray Diffraction (XRD), Energy dispersive X-ray diffraction spectroscopy (EDS). The size of biogenic nanoparticles ranges 5-20 nm. The antimicrobial activity of silver nanoparticles was evaluated using Agar well diffusion method. The results showed that the silver nanoparticles exhibit significant antibacterial activity.